FLYPAPER EFFECT PADA DANA ALOKASI UMUM DAN PENDAPATAN ASLI DAERAH TERHADAP BELANJA DAERAH BONDOWOSO - Prahesti, Alifani Indah (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the existence of flypaper effect on the local ownsourcerevenue and general allocation fund to the Bondowoso regency local expenditure based on theanalysis of the realization of local government budget report of the local government of Bondowosoregency which is conducted by using financial ratio. Based on the result of analysis and the discussionwhich has been performed in order to find out the flypaper effect on the local own-source revenue andlocal allocation fund to the Bondowoso regency local expenditure by using financial ratios analysiswhich consist of: (1) local revenue analysis which include (a) the decentralization degree ratio showslow result â¤ 50% with the tendency of increasing, (b) the dependency ratio of local financial to thegeneral allocation fund shows high result â¥ 50% with the tendency of increasing, (c) the independencyratio of local revenue shows low result â¤ 50% with the tendency of increasing, (d) the growth ratio oflocal own-source revenue shows positive growth with the tendency of increasing, (e) the growth ratioof general allocation fund shows growth which tend to increase; (2) the growth ratio of localexpenditure shows growth with the tendency to increase; (3) the analysis of revenue performancewhich includes (a) effectiveness ratio of local own-source revenue has a very effective level ofeffectiveness which always fulfills the target (100% - â¥ 100%), (b) the efficiency ratio of generalallocation fund has inefficient result (100% - â¥100%).Keywords: Flypaper Effect, Local Own-Source Revenue, General Allocation Fund, and Local Expenditure